Effects of carbonated natural mineral water baths and mofettes on peripheral arterial flow in rats - Gabriela Dogaru; Constantin Munteanu; Bianca Pop; Lorena Ciumărnean; Luciana Mădălina Gherman; Alina Deniza Ciubean; Adela-Viviana Sitar-Tăut (Balneo and PRM Research Journal, 2023)
(1) Introduction. Disorders of peripheral blood circulation affect people all around the world. Balneotherapy, in the form of carbonated mineral water baths and mofettes, could be considered one of the treatment options. The current study aims to investigate, in an experimental study, the effects of carbonated natural mineral water, with a known composition, and natural mofettes from Băile Tușnad (Romania) on peripheral arterial blood flow. (2) Material and method. A total of 16 rat subjects were studied, divided equally into 4 groups, all evaluated at 2, 4 and 6 weeks after the intervention. Group 1 was considered the control-group, and no treatment was applied. Group 2 was taken to the mofettes daily, for 2 weeks, for exposure to carbon dioxide, dry gas, for 20 minutes/day. Group 3 performed daily mofettes and baths with carbonated mineral water, for two weeks, 20 minutes/day, each procedure. Group 4 took a daily bath with carbonated mineral water, for 2 weeks, 20 min/day. At the end of the two-week treatment, they were evaluated by doppler ultrasound at the femoral artery, respectively at 2 and 4 weeks, to evaluate the effect over time of these treatments. Femoral artery diameter (mm), peak systolic velocity (PVS, cm/s), heart rate (HR, bpm) were quantitatively determined in all 4 groups, at 2, 4 and 6 weeks respectively, and ultrasound images were captured. (3) Results and discussions. In the control group, there were no differences at 2 weeks vs. 4 weeks vs. 6 weeks regardless of the studied parameter. The diameter of the femoral artery increased significantly in group 3 (mofetta and carbonated mineral water, p=0.0183), respectively in group 4 (mineral water p=0.007). Heart rate changed significantly p=0.0183 in the mofette group, as well as in the one treated with carbonated mineral water p= 0.024. The results of the study suggest that carbonated mineral water and mofettes were responsible for the changes in femoral artery flow, compared to the data from the control group. (4) Conclusions. Carbonated mineral water baths and mofettes could increase the peripheral arterial blood flow, during repeated immersion, and the results were beneficial 2 weeks after the end of the treatment, and were maintained after treatment at 4 and 6 weeks, respectively